Mary Poppins returns [compact disc] : [Original motion picture soundtrack] - Shaiman, Marc (Walt Disney Records, 2018)
Marc Shaiman and Scott Wittman, the team behind the musical Hairspray, create magical music moments for Mary Poppins's return to the big screen. Included are performances by cast including Emily Blunt and Lin-Manuel Miranda.